Manajemen Perpustakaan Berbasis Information and Communication Tecnology (ICT) di Universitas Muslim Nusantara Al –Washliyah - Mawaddhah, Azzura; Achiriah, Achiriah; Farthurrahman, Muslih (ARZUSIN, 2024)
This study aims to determine ICT-based library management because the rapid development of technology makes significant changes, especially in information technology. Related to the development of information technology, libraries have also changed from conventional libraries to digital libraries. Library as an information center in the face of technological developments, namely by managing libraries using library management based on Information and Communication Technology (ICT) as library management. This development can be felt now with many libraries using Infomation and Communication Technology (ICT) as management in libraries. This type of research is descriptive with qualitative methods. The techniques used for data collection are interviews, observation, and documentation. Data analysis using three stages, namely: data reduction, presentation, and conclusions. The results of this study show that ICT-based library management is able to improve services and use in libraries, as well as make it easier for students to obtain books and information needed because in its services it does not have a difficult process but is faced with a lack of human resources (Human Resources) in ICT management.